Signaling to NF-κB: Regulation by Ubiquitination - Wertz, Ingrid E. (Cold Spring Harbor Laboratory Press, 2010)
The NF-κB pathway is a ubiquitous stress response that activates the NF-κB family of transcription factors. Antigen receptors, receptors of the innate immune system, and certain intracellular stressors are potent activators of this pathway. The transcriptional program that is activated is both antiapoptotic and highly proinflammatory. Indeed, any compromise in engagement of the pathway results in immunodeficiency, whereas constitutive activation generates a sustained inflammatory response that may promote malignancy. As such, NF-κB activation is under tight regulation by a number of post-translational modifications, including phosphorylation and ubiquitination. This article attempts to synthesize our current knowledge regarding the regulation of NF-κB signaling by ubiquitination, specifically highlighting the biochemical basis for both positive and negative feedback loops that function in unison to generate coordinated signals that are essential for the viability of metazoan animals.